Study of foil explosion using the soft x-ray radiography. (May 2020) - Zhigalin, A S; Oreshkin, V I; Rousskikh, A G; Baksht, R B
Abstract: The experiments were carried out upon a research facility comprising three current generators. One of them was used to initiate the explosion of a foil and the other two, X-pinch backlighting sources were used for diagnostics. In the experiments, an upper limit has been determined for the decay time of the metastable state of a superheated metal. For aluminum, at a foil thickness of 6 μ m and a deposited energy of 5.3 ± 0.5 kJ/g, the metastable state decay time was about 90 ns; for copper, at the same foil thickness and a deposited energy of 2.1 ± 0.3 kJ/g, it was about 250 ns; for nickel at the same foil thickness and a deposited energy of 1.3 ± 0.4 kJ/g, it was about 390 ns.